The Video Head Impulse Test and the Influence of Daily Use of Spectacles to Correct a Refractive Error - van Dooren, T.S.; Lucieer, F.M.P.; Janssen, A.M.L.; Kingma, H.; van de Berg, R. (Frontiers in Neurology, 2018)
Abstract Objective: To determine the influence of daily use of spectacles to correct a refractive error, on the VOR gain measured with the video head impulse test (vHIT). Study design: This prospective study enrolled subjects between 18 and 80 years old with and without a refractive error. Subjects were classified into three groups: (1) contact lenses, (2) spectacles and (3) control group without visual impairment. Exclusion criteria comprised ophthalmic pathology, history of vestibular disorders and alternated use of spectacles and contact lenses in daily life. Corrective spectacles were removed seconds before testing. One examiner performed all vHIT’s under standardized circumstances using the EyeSeeCam system. This system calculated the horizontal VOR-gain for rightward and leftward head rotations separately. Results: No statistically significant difference was found in VOR gain between the control group (n=16), spectacles group (n=48) and contact lenses group (n=15) (p = 0.111). Both the spectacles group and contact lenses group showed no statistically significant correlation between VOR gain and amount of refractive error, for rightwards (p= 0.071) and leftwards (p= 0.716) head rotations. There was no statistical significant difference in VOR gain between testing monocularly or binocularly (p = 0.132) and between testing with or without wearing contact lenses (p = 0.800). Conclusion: In this study VOR gain was not influenced by wearing corrective spectacles or contact lenses on a daily basis. Based on this study, no corrective measures are necessary when performing the vHIT on subjects with a refractive error, regardless of the way of correction.